Why Philosophers Aren’t Better People - Dwyer, James (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
I begin with an autobiographical account that explains the question: why philosophers are not better people. Philosophy, as it is practiced in most university departments, doesn’t concern itself with how we inhabit and perceive the world. It doesn’t really concern itself with practices that aim to form the kind of people we become. After I discuss why the question still resonates today, I consider one answer, based on some work by John Dewey. His work emphasizes the importance of habits. Since habits are formed in social environments, the discussion of habits leads me to consider the practice of politics: the idea that we could collectively shape social environments in which habits are formed. Although I do not deny that the practice of politics can be burdensome and dangerous, I try to show why this practice is inevitable.